P0486THROMBOTIC MICROANGIOPATHY IN A PATIENT WITH PERSISTENT CRYOGLOBULINEMIA AFTER HCV ERADICATION AND HETEROZYGOUS DELETION OF CFHR3-CFHR1 REGION: SHOULD WE TREAT WITH RITUXIMAB, ECULIZUMAB OR PLASMAPHERESIS?. (6th June 2020) - Gallo, Pamela; Gallo, Pamela; Somma, Chiara; Zullo, Claudia; Lombardi, Marco; Ferro, Giuseppe; Dattolo, Pietro Claudio
Abstract: Background and Aims: Mixed cryoglobulinemia type II is a systemic vasculitis, caused by deposition of immune complexes in the endothelium of small vessels. Up to 90% are HCV infection related and usually resolve after eradication of the virus. Method: We report the case of a patient with HCV related type II cryoglobulinemia, persistent despite the eradication of the virus with sofosbuvir and complicated by thrombotic microangiopathy. Results: Since 2001 patient had cryoglobulinemic vasculitis treated with rituximab in 2002 and in 2011 for a relapse. In 2015 started antiviral therapy with sofosbuvir achieving sustained viral remission. In December 2018 she admitted to hospital for fever, abdominal pain, diarrhea and oedema. Blood exams showed acute kidney injury, (scar 3 mg/dl) proteinuria (2, 6 g/24h) e microhematuria, haemolytic anaemia and thrombocytopenia, low C4, rheumatoid factor, cryocrit 4% (type II cryoglobulinemia), ANA, ENA e HCV RNA were negatives. On renal biopsy we found a thrombotic microangiopathy (fig.1, 2). We rule out a lymphoma through PET total body e immunophenotype. Conclusion: This report shows persistent cryoglobulinemia with vasculitis relapses, after HCV eradication with direct antiviral therapy (fig. 3), paying attention to complexity of immunological response, causing in this patient a TMA. Intriguing in our report is the finding of TMA on renal biopsy, without other lesions, contrary to what expected. Cryoglobulinemic vasculitis are usually associated to membranoproliferative glomerulonephritis. For this reason we search genetic mutation of complement genes, finding a heterozygous deletion on CHFR3-CHFR1 region. A pathogenic role of this deletion, is unknown, but it could mean a different target of therapy.